Elevated TyG index associated with increased prevalence of gallstones in a United States cross-sectional study - Feng, Xueyi; Wu, Shenwei; Ke, Bin; Liang, Yongkang (Frontiers in Public Health, 2024)
Objective: This study aimed to investigate the correlation between the triglyceride-glucose (TyG) index and the incidence of cholelithiasis Research Approach: In this investigation, a cross-sectional analysis was undertaken utilizing data from the US National Health and Nutrition Examination Survey (NHANES) spanning the years 2017 to 2020. The TyG index served as an independent predictor, while gallstone prevalence was considered the dependent variable of interest. We employed a multivariate logistic regression model to evaluate the interplay between these independent and dependent variables. To assess the presence of potential non-linear associations, sensitivity analysis was executed, utilizing inverse probability weighted validation, smooth curve fitting, and threshold effect analysis. In cases where non-linear relationships were observed, likelihood ratios were utilized to pinpoint potential inflection points. Ultimately, subgroup analyses were conducted to identify specific populations demonstrating heightened susceptibility to gallstone prevalence.Encompassing 838 patients who self-reported gallstones, a total of 7794 participants were included in the analytical cohort. A statistically significant disparity in the TyG index was observed when all individuals were categorized into gallstone patients and non-patients (p < 0.05). Logistic regression findings indicated a positive correlation between the TyG index and gallstone disease prevalence (OR = 1.28, 95% CI: 1.12, 1.47), with a strengthening association as the TyG index increased (p trend < 0.01). The results were corroborated by the use of inverse probability weighting.Additionally, a non-linear connection between the TyG index and gallstone prevalence was identified (log-likelihood ratio p < 0.01), with the optimal inflection point for TyG calculated at 8.96. In subgroup analysis, the positive relationship between the TyG index and gallstone prevalence was notably pronounced among black Americans under the age of 40 and female participants Conclusion: Alterations in the TyG index may potentially correlate with shifts in the prevalence of gallstones among adult populations in the United States. Elevated TyG index values may coincide with an augmented likelihood of gallstone occurrence.